Perceived Personality Traits of Deaf Students of Cagayan de Oro National High School: Basis for Intervention - Jelvett Mynne Faelden (Philippine Association of Institutions for Research, Inc., 2019)
Deafness is one of the factors which affects social, emotional, intellectual, and even the psychological aspect of a person. In general, it affects the person holistically and, thus, affects personality. Deaf students pose many challenges in their lives, difficulty in hearing, inability to express themselves and to communicate the people that surround them. The core problem is communication difficulties which are the clear barrier in the social relationships with their peers. The study was conducted to describe the perceived personality traits-related problems of the deaf students of Cagayan de Oro National High School (CNHS), Cagayan de Oro City. The study utilized the descriptive research design and survey questionnaires were given to the deaf students, parents, and teachers. The data were analyzed using descriptive statistics as frequency, percentage, t-test, and ANOVA. Deaf students were neutral in four dominant personalities, conscientiousness, agreeableness, and neuroticism. Further, the teachers were more committed than parents in the development of the deaf students' personality traits related problems.